Gambaran Psikososial Pemandu Karoke di Sarirejo, Salatiga - Desi Desi; Caroline Surjadi; Sri Suwartiningsih (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2022)
Identical to the physical appearance that is demanded to be attractive, work activities are carried out all night and the service orientation is mostly related to male customers, making Karaoke Guide workers judged negatively by the surrounding community. This condition has an impact on the psychosocial condition of Karaoke Guide workers. The purpose of this study was to describe the psychosocial condition of karaoke guides in their environment. This research method is qualitative with a descriptive approach. The research participants were 5 karaoke guide workers with an age range of 17-30 years. This research was conducted at a karaoke tourist location in Sarirejo Village-Salatiga. The result of this study is that the karaoke driver shows that the psychosocial changes of the karaoke driver are motivated by stigma. Meanwhile, the selection of karaoke guides as their main job is based on their educational background and daily needs. Conclusion: The conclusion of this study is that the psychosocial karoke guides experience problems caused by the stigma of society.